Inflation Targeting and Output Stability - Jadresic, Esteban (IMF Working Papers; Working Paper, 1999)
This paper reexamines the effects of inflation targeting on output stability. It considers an economy with staggered price setting that is exposed to price shocks and where the policymaker cannot observe the current realizations of aggregate output and inflation. The paper shows that, if some price shocks can be anticipated, the effects of inflation targeting depend critically on the inflation indicator being targeted. Specifically, targeting headline inflation can severely destabilize output, while targeting inflation indicator of sticky prices may eliminate that problem and make the response of the output gap to aggregate shocks short-lived.